The evaluation of some hematological parameters of human tuberculosis in Thi-Qar Province - Manal Al-Tamemi (University of Thi-Qar Journal of Science, 1970)
The present study aimed to evaluation of erythrocyte sedimentation rate (ESR), hemoglobin (Hb.) levels, whiteblood cell count (WBCs) in active and latent tuberculosis patients in Thi-Qar province,Iraq. This study included 210samples (70 patients, 70 household contacts and 70 control ) with age's ≤10 to ≥70 years who were referred to ALNasiriyaCenterofTuberculosisandChestDiseasesfromtheperiodSeptember2012—July2013.The studyshowed thatthevalues erythrocyte sedimentation rate indicated a significant increase (P≤0.05) in patients and HHCs groups whencompared with the value of control group (42.64, 22.93 vs. 8.79 mm/h, respectively). While the results showed asignificant decrease (P≤0.05) in the hemoglobin, (Hb.) levels of patients group and HHCs when compared with controlgroup (8.63 and 11.84 vs.13.17 gm/dl, respectively). The means of white blood cell (WBCs), showed a significantincrease in patient and household when compared with correspondent value of control groups.